Preclinical comparison of [177Lu]Lu-rhPSMA-10.1 and [177Lu]Lu-rhPSMA-10.2 for endoradiotherapy of prostate cancer: biodistribution and dosimetry studies - Alexander Wurzer; Francesco De Rose; Sebastian Fischer; Markus Schwaiger; Wolfgang Weber; Stephan Nekolla; Hans-Jürgen Wester; Matthias Eiber; Calogero D'Alessandria (SpringerOpen, 2024)
Abstract Background Radiohybrid PSMA-targeted ligands (rhPSMA) have been introduced as a novel platform for theranostic applications. Among a variety of rhPSMA-ligands developed for radioligand therapy, two stereoisomers [177Lu]Lu-rhPSMA-10.1 and -10.2 have been synthesized and initially characterized in preclinical experiments with the aim to provide an optimized binding profile to human serum albumin, a reduction of charge, and thus accelerated kidney excretion, and unaffected or even improved tumor uptake. As both isomers showed similar in vitro characteristics and tumor uptake at 24 h post injection in tumor bearing mice and in order to identify the isomer with the most favorable pharmacokinetics for radioligand therapy, we carried out in-depth biodistribution and dosimetry studies in tumor-bearing and healthy mice. Results rhPSMA-10.1 and -10.2 were radiolabeled with lutetium-177 according to the established procedures of other DOTA-based PSMA ligands and displayed a high and comparable stability in all buffers and human serum (> 97%, 24 h). Biodistribution studies revealed fast clearance from the blood pool (0.3-0.6%ID/g at 1 h) and other background tissues within 48 h. Distinctive differences were found in the kidneys, where [177Lu]Lu-rhPSMA-10.1 displayed lower initial uptake and faster excretion kinetics compared to [177Lu]Lu-rhPSMA-10.2 expressed by a 1.5-fold and ninefold lower uptake value at 1 h and 24 h in healthy animals, respectively. Tumor uptake was comparable and in the range of 8.6-11.6%ID/g for both isomers over 24 h and was maintained up to 168 h at a level of 2.2 ± 0.8 and 4.1 ± 1.4%ID/g for [177Lu]Lu-rhPSMA-10.1 and [177Lu]Lu-rhPSMA-10.2, respectively. Conclusion Our preclinical data on biodistribution and dosimetry indicate a more favorable profile of [177Lu]Lu-rhPSMA-10.1 compared to [177Lu]Lu-rhPSMA-10.2 for PSMA-targeted radioligand therapy. [177Lu]Lu-rhPSMA-10.1 shows fast kidney clearance kinetics resulting in excellent tumor-to-organ ratios over a therapy relevant time course. Meanwhile, [177Lu]Lu-rhPSMA-10.1 is currently being investigated in clinical phase I/II studies in patients with mCRPC (NCT05413850), in patients with high-risk localized PC (NCT06066437, Nautilus Trial) and after external beam radiotherapy (NCT06105918).